2003
DOI: 10.1037/1099-9809.9.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Mediational models of spirituality and depressive symptomatology among HIV-positive Puerto Rican women.

Abstract: A survey of 142 Puerto Rican women living with HIV/AIDS in New York City revealed high Centers for Epidemiological Studies Depression (CES-D) scores, with 66% of the sample scoring above the conventional threshold of possible clinical depression. Most respondents (71%) were Catholic, 29% considered themselves members of a church or other place of worship, and 30% reported attending religious services 1-3 times a month. As predicted, spirituality was high and negatively associated with CES-D scores. A series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 34 publications
6
74
1
4
Order By: Relevance
“…Although statistical analyses of differences were not conducted, the participants in this study seemed to endorse religious coping items higher than a sample of medically ill patients (see Pargament et al, 2004) on six of the seven dimensions of interest in current the study. This finding is consistent with literature which suggested that Latinas and Latinos are likely to turn to religion as a coping mechanism (e.g., Abraído-Lanza, 2004;Mausbach et al, 2003;Santiago-Rivera, 2005;Simoni & Ortiz, 2003).…”
Section: Analysis Of Religious Coping and Psychological Outcomessupporting
confidence: 82%
See 1 more Smart Citation
“…Although statistical analyses of differences were not conducted, the participants in this study seemed to endorse religious coping items higher than a sample of medically ill patients (see Pargament et al, 2004) on six of the seven dimensions of interest in current the study. This finding is consistent with literature which suggested that Latinas and Latinos are likely to turn to religion as a coping mechanism (e.g., Abraído-Lanza, 2004;Mausbach et al, 2003;Santiago-Rivera, 2005;Simoni & Ortiz, 2003).…”
Section: Analysis Of Religious Coping and Psychological Outcomessupporting
confidence: 82%
“…Another recent study of Puerto Rican women living with HIV highlighted the importance of spirituality as a buffer against depression (Simoni & Ortiz, 2003). Overall, Latinas reported high levels of spirituality, and reported attending religious services with some regularity.…”
Section: Religious Copingmentioning
confidence: 99%
“…Therefore, fatalism, as rooted in religious beliefs, may be better represented with themes related to acceptance, as in "what God sends, one has to accept" [18, p. 441], or to frameworks for interpreting events in terms of a greater purpose or "grander plan" [31, p. 55]. The connection between religiosity and fatalism may be particularly salient among some Latino groups, for whom religiosity is embedded in an overarching belief system that helps individuals to cope with stressful events, and promotes physical and psychological well-being [32][33][34][35][36]. Religious beliefs centering on God as a "partner" [37] may actually counteract fatalistic tendencies by increasing Latinos' sense of mastery and ability to cope with disease by providing hope in their lives, and by strengthening self-esteem and social support networks.…”
Section: Discussionmentioning
confidence: 99%
“…Estos síntomas fueron relacionados con un estado de salud deteriorado, con inadecuadas percepciones acerca de la enfermedad (15,16), menor apoyo social, y menor bienestar espiritual (17,18). En lo que concierne al modelo paciente-enfermedad, ya se ha expuesto que si hay altos niveles de depresión en el paciente, esto puede llevar a disminuir los recuentos celulares de linfocitos CD 4 (19,20), los cuales son la base del deterioro del sistema inmunológico y su disminución ocasiona una inmunosupresión con las correspondientes infecciones oportunistas que se pueden desarrollar.…”
Section: Contexto Generalunclassified